THE ROLE OF TRADITIONAL LEADERSHIP AND COMMUNICATION DYNAMICS IN MAINTAINING THE CULTURAL HERITAGE OF THE BADUY TRIBE - Idris, Julizar (Yayasan Education and Social Center, 2023)
The primary objective of this study is to investigate the significance of traditional leadership and communication dynamics in the preservation of the cultural heritage of the Baduy tribe. The Baduy tribe, which resides in the Banten Province of Indonesia, possesses a culturally rich and distinctive heritage. However, the impact of modernization and social change has affected the preservation of their culture. This research method uses a qualitative approach by collecting data through in-depth interviews, observation and document analysis. The research findings indicate that traditional leadership plays a crucial role in the preservation and perpetuation of Baduy culture. In Baduy society, the role of traditional leaders encompasses the preservation of cultural customs, the establishment of regulatory frameworks, and the facilitation of communication channels. This study posits that the interconnectedness of traditional leadership and communication dynamics plays a crucial role in the preservation of the cultural heritage of the Baduy tribe. The success in preserving the cultural heritage of the Baduy tribe in the face of modernization is contingent upon the collaborative endeavours between traditional leaders and community members, which encompass the preservation of traditions and the facilitation of communication. This study offers significant contributions to the understanding of strategies for preserving traditional culture amidst the challenges posed by rapid social and environmental transformations